THE PLACE OF THE BLACK WOMAN AND THE ANALYST IN BRAZIL: A CLINICAL-POLITICAL ESSAY OF THE BLACK FUNCTION OF LISTENING - Paulon, Clarice Pimentel; Barbosa, Thamires Kelly Andrade (Fundacao Univ Tocantins, 2023)
This clinical-political essay intends to strain the historical articulations of Brazil concerning the place of blackness, in particular, of the black woman. Through the way in which Gonzalez uses the notion of memory, bringing up current materialities of the Brazilian racist daily life, also psychoanalysis in the clinic does so with various historical-unconscious content. We can address the place of the black Brazilian woman as the analyst in Brazil. Her position and the transference possibilities developed with her, produce a material listening regarding subjectivities, all crossed by the myth of this woman. The black woman is object a, just as the analyst's position should be. She is in the centrality of the Brazilian Oedipus and, also, in the eroticism of the culture. Addressing analytical questions to this woman who, in her exteriority, sustains the fantasy of the identity of the Brazilian people, produces effects of remembrance and resignification for a Brazil that can discover itself and be another.
Keywords: Clinic; Politics; Memory; Black Woman; Transference